SOME ASPECTS OF EXAMINING THE IMAGES OF TRACER HYPERFIXATION FOCI IN OSTEOSCINTIGRAMS BY COMPUTER-ASSISTED AUTOMATED ANALYSIS - N. E. Kosykh; S. Z. Savin; V. L. Kovalenko; T. P. Potapova; K. A. Litvinov (Вестник рентгенологии и радиологии)
Objective: to analyze the numerical characteristics of bone metastases according to scintigraphic data. Material and methods. Computer-assisted automated analysis was used to examine planar skeletal osteoscintigrams in patients with breast cancer who had both complete remission and disease progression with skeletal metastases. Brightness in the image was used as an analyzed indicator. Results. Examination of physiological tracer accumulation in patients without skeletal metastases suggests that there is a wide variability of brightness values in the scintigrams of individual skeletal areas. At the same time, the skeletal anatomic areas show significant differences in the average image brightness values (p<0.01). In virtually all skeletal areas, the average brightness values in the pathological tracer hyperfixation foci (HFFs) in the scintigrams are dominant over the similar values of physiological HFFs. Conclusion. There is a direct relationship between the tracer accumulation levels in the skeletal areas without metastatic involvement and the bone metastases occurring in the same areas.